ANALISIS PENGARUH HARGA PATOKAN EKSPOR CRUDE PALM OIL (CPO) DAN KURS TERHADAP PENERIMAAN BEA KELUAR PADA KPPBC TMP B PALEMBANG PERIODE 2019-2024 - Alif Maulana Ibrahim; Silvana Syah (PT. Hasba Edukasi Mandiri, 2025)
This study aims to analyze the effect of the export reference price of Crude Palm Oil (CPO) and the USD exchange rate on export duty revenue at the Customs and Excise Office Type Madya Pabean B Palembang. The research employs a quantitative approach using multiple linear regression analysis. The data used are monthly secondary data from January 2019 to December 2024, sourced from official institutions such as the Ministry of Trade, Bank Indonesia, and the Directorate General of Customs and Excise. The results indicate that both the export reference price and the USD exchange rate have a positive and significant effect on export duty revenue, both partially and simultaneously. The regression model used is able to explain a substantial portion of the variation in export duty revenue over time. The study concludes that price and exchange rate dynamics are key factors in optimizing state revenue from the export sector.